(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
Chains of disconcerting revolutions that engulfed the Arab World years back indicated the willingness of the citizenry to bring the years of denial, corruption, humiliation, oppression to a hasty end. This event started off with Tunisia in December 2010. The magnitude with which it speeded to other countries coupled with the debilitating consequences it left behind engulfed the attention of scholars, politicians, to mention but two. Using Tunisia’s revolution as a case study. The overriding purpose of this research paper was to determine the underlying factors behind the Arab spring, with a particular attention on Islamism as a factor. Using the existing literature, this paper concluded that, the series of uprisings that engulfed the Arab countries had Islamism agenda or Islamists elements behind it, and that other factors were symptoms of the profound weakened political structure across the Arab countries for ages. It would, therefore, not be proper to relegate Islamism in these events. The study, therefore, called on future researchers to critically look into the underlying factors leading to Arab Spring using quantitative methods with open-ended questions, and with special attention on Political Islam.